Can Essentiality of Origin Save Meritocracy From The Luck Objection? - Napoletano, Toby (Philosophia, 2023)
Rawls famously argued against meritocratic conceptions of distributive justice on the grounds that the accumulation of merit is an unavoidably lucky process, both because of differences in early environment, and innate talents. Thomas Mulligan (2018a) has recently provided a novel defense of meritocracy against the "luck objection", arguing that both sources of luck would be mostly eliminated in a meritocracy. While a system of fair equality of opportunity ensures that differences in social class or early environment do not lead to differences in the accumulation of merit, Kripke's essentiality of origin thesis means that our genetic endowments, and thus our innate talents, could not have been any other way. But if we could not fail to have our innate talents, Mulligan argues, then it is not a matter of luck that we have them, and so the merits we accumulate on their basis are not so luck-dependent. This paper argues that Mulligan's appeal to the essentiality of origin thesis fails to rescue meritocratic conceptions of distributive justice from the luck objection for two reasons. First, even granting essentiality of origin and fair equality of opportunity, the contingencies of the market and the social environment mean that having some innate talents is far luckier than having others. And second, the appeal to essentiality of origin misses the underlying motivation for the luck objection, and ignores the intimate connection between desert and responsibility.